2020
DOI: 10.1038/s41598-020-60993-5
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms synthesize sterols by inclusion of animal and fungal genes in the plant pathway

Abstract: Diatoms are ubiquitous microalgae that have developed remarkable metabolic plasticity and gene diversification. Here we report the first elucidation of the complete biosynthesis of sterols in the lineage. The study has been carried out on the bloom-forming species Skeletonema marinoi and Cyclotella cryptica that synthesise an ensemble of sterols with chemotypes of animals (cholesterol and desmosterol), plants (dihydrobrassicasterol and 24-methylene cholesterol), algae (fucosterol) and marine invertebrates (cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…Moreover, a fatty acid mixture, showing the presence of saturated and unsaturated fatty acids with a chain length of C 12 to C 22 , being rich in C 16 and C 18 acids as active constituents in antifouling activity [97]. (Figure 5), β-sitosterol (stigmasta-5-en-3β-ol) (39) [48], and β-cholestanol (5α-cholestan-3βol) (107) [99] were identified and sterol 39 in this study [97] was found to contain 35% of a 24S epimer (clionasterol) (108) [100,101] (Figure 17). Sterol 39 had the highest antifouling activity among sterols 26, 39, and 107 [97].…”
Section: Dendronephthya Sppmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, a fatty acid mixture, showing the presence of saturated and unsaturated fatty acids with a chain length of C 12 to C 22 , being rich in C 16 and C 18 acids as active constituents in antifouling activity [97]. (Figure 5), β-sitosterol (stigmasta-5-en-3β-ol) (39) [48], and β-cholestanol (5α-cholestan-3βol) (107) [99] were identified and sterol 39 in this study [97] was found to contain 35% of a 24S epimer (clionasterol) (108) [100,101] (Figure 17). Sterol 39 had the highest antifouling activity among sterols 26, 39, and 107 [97].…”
Section: Dendronephthya Sppmentioning
confidence: 78%
“…Purification of the extract gave mixtures of sterols and fatty acids as active components. In the sterol mixture, there are several sterols, (24 S )-24-methylcholesta-5( E ),22- dien-3β-ol (= pincsterol) or (24 R )-24-methylcholesta-5( E ),22-dien-3β-ol (= brassicasterol) ( 106 ) [ 98 ], cholesterol ( 26 ) [ 30 ] ( Figure 5 ), β-sitosterol (stigmasta-5-en-3β-ol) ( 39 ) [ 48 ], and β-cholestanol (5α- cholestan-3β-ol) ( 107 ) [ 99 ] were identified and sterol 39 in this study [ 97 ] was found to contain 35% of a 24 S epimer (clionasterol) ( 108 ) [ 100 , 101 ] ( Figure 17 ). Sterol 39 had the highest antifouling activity among sterols 26 , 39 , and 107 [ 97 ] .…”
Section: Dendronephthya Sppmentioning
confidence: 98%
“…The biosynthetic pathway from cycloartenol to 24-methylcholest-22-enol shares many steps with the classical land plant biosynthesis pathway from cycloartenol to campesterol ( Desmond and Gribaldo, 2009 ), the main difference being that as for the pathway from cycloartenol to cholesterol, the second sterol-4-demethylation is inferred here to occur before the sterol-Δ 8 -Δ 7 -isomerization. The pathway leading to fucosterol may end up in a diatom-like way with a sterol-5-desaturation and a sterol-Δ 7 -reduction following a sterol-28-methylation leading to different epimers than in land plants ( Gallo et al, 2020 ). However, since the main biochemical requirement for sterol side chain alkylation at carbons 24 and 28 is the presence of a Δ 24(25) or Δ 24(28) double bond ( Nes, 2003 ), alternative routes may be possible from other precursors having those double bonds (dotted arrows on Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The associated biosynthetic pathways are good models to study metabolic pathway evolution because the enzymes involved are well-known across eukaryotes and relatively conserved despite some variation ( Desmond and Gribaldo, 2009 ). Recently, several studies have enabled to better understand the history of this pathway in land plants ( Sonawane et al, 2016 ), diatoms ( Gallo et al, 2020 ), or red algae ( Belcour et al, 2020 ). However, a general model for sterol biosynthesis in brown algae – a vast diversified and independent eukaryotic lineage ( Bringloe et al, 2020 ) – is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in Fiji, Samoa and Tonga the market value reached by the harvested alga is estimated about USD 270,000 per year resulting in a production of over 120 tonnes of fresh Caulerpa , which plays a crucial role in the economy of these countries [ 13 ]. In recent years, Caulerpa species may be highly economically useful as they can be readily used for the production of bio-compounds for nutraceutical, pharmaceutical and cosmetic purposes [ 4 , 5 , 14 , 15 , 16 , 17 ]. Caulerpa produces interesting metabolites, namely caulerpin, sulfated polysaccharides (SP), racemosin, alkaloids, xyloglucans and fatty acid derived products, which are highly desirable for commercial purposes, and are not fully commercially exploited yet [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%